Horizontal gene transfer of a ColV plasmid has resulted in a dominant avian clonal type of Salmonella enterica serovar Kentucky. - Timothy J Johnson (Public Library of Science (PLoS), 2010)
Salmonella enterica continues to be a significant cause of foodborne gastrointestinal illness in humans. A wide variety of Salmonella serovars have been isolated from production birds and from retail poultry meat. Recently, though, S. enterica subsp. enterica serovar Kentucky has emerged as one of the prominent Salmonella serovars isolated from broiler chickens. Recent work suggests that its emergence apparently coincides with its acquisition of a ColV virulence plasmid. In the present study, we examined 902 Salmonella isolates belonging to 59 different serovars for the presence of this plasmid. Of the serovars examined, the ColV plasmid was found only among isolates belonging to the serovars Kentucky (72.9%), Typhimurium (15.0%) and Heidelberg (1.7%). We demonstrated that a single PFGE clonal type of S. Kentucky harbors this plasmid, and acquisition of this plasmid by S. Kentucky significantly increased its ability to colonize the chicken cecum and cause extraintestinal disease. Comparison of the completed sequences of three ColV plasmids from S. Kentucky isolated from different geographical locales, timepoints and sources revealed a nearly identical genetic structure with few single nucleotide changes or insertions/deletions. Overall, it appears that the ColV plasmid was recently acquired by a single clonal type S. Kentucky and confers to its host enhanced colonization and fitness capabilities. Thus, the potential for horizontal gene transfer of virulence and fitness factors to Salmonella from other enteric bacteria exists in poultry, representing a potential human health hazard.